Reflector Antenna reCeiving a spherical wave - O. A. Yurtsev; N. M. Naumovich; M. M. Dgali (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paraboloidal reflector antenna is considered. The feed element is a horn. Using physical optics (PO) method the near field distribution and antenna pattern are studied when the antenna is focused to near-field and far-field region.